Field inoculation of arbuscular mycorrhiza on maize (Zea mays L.) under low inputs: preliminary study on quantitative and qualitative aspects - Emilio Sabia; Salvatore Claps; Giuseppe Morone; Annarita Bruno; Lucia Sepe; Riccardo Aleandri (Italian Journal of Agronomy)
Arbuscular mycorrhizal symbiosis contributes to the sustainability of soil-plant system. A field experiment was conducted to examine the effect of arbuscular mycorrhiza (AM) on quantitative and qualitative performance in forage maize (Zea mays L.). Within the project Sviluppo di modelli zootecnici ai fini della sostenibilità (SOS-ZOOT) a trial was conducted at the experimental farm of the Agricultural Research Council in Bella (PZ), located in Basilicata region (Southern Italy) at 360 m asl, characterised by an annual rainfall of approximately 650 mm. For spring sowing, two plots of 2500 m2 were used, one sown with seeds inoculated with AM (M), 1.0 kg/ha, and the other one with non-inoculated seeds (NM). After 120 days after sowing, when plants showed 30% dry matter, five replicates of 1 m2 per plot were used to estimate dry matter yield (DMY), while half plot was dedicated to the assessment of grain production. For each replicate, three representative plants were considered; each plant was measured for height and was divided into leaves, stem and ear. For each plot, the following constituents were determined: crude protein, ash, ether extract, crude fibre (CF), fractions of fibre [neutral detergent (NDF), acid detergent fibre (ADF) and sulphuric acid lignin] and phosphorus (P). Throughout the period of plants’ growth, no herbicides, organic or inorganic fertilisation, and irrigation water were distributed. The preliminary results revealed a significant effect of AM inoculation on forage maize DMY, P content in the whole plant, into the leaves and on the quality of steam. The M thesis showed a significant increase in terms of DMY in comparison with the NM thesis: 21.2 vs 17.9 t/ha (P<0.05). The mycorrhized whole plants [0.22 vs 0.17% dry matter (DM), P<0.05] and leaves (0.14 vs 0.09% DM, P<0.05) showed an increased P content. The stems of M plants showed a content of CF, NDF, ADF and Ash significantly lower compared with NM plants. No significant differences were observed for the other parameters. The preliminary study revealed a significant effect of AM seed inoculation on DMY and quality of forage maize cultivated within a low input system.